2019
DOI: 10.1128/msystems.00211-19
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Primary Antimicrobial Resistance Drivers in Agricultural Nontyphoidal Salmonella enterica Serovars by Using Machine Learning

Abstract: Nontyphoidal Salmonella (NTS) is a leading global cause of bacterial foodborne morbidity and mortality. Our ability to treat severe NTS infections has been impaired by increasing antimicrobial resistance (AMR). To understand and mitigate the global health crisis AMR represents, we need to link the observed resistance phenotypes with their underlying genomic mechanisms. Broiler chickens represent a key reservoir and vector for NTS infections, but isolates from this setting have been characterized in only very l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…Other studies attempted the analysis of antimicrobial resistance on E . coli with machine learning and larger sample sizes [ 20 , 26 , 27 , 86 ]. However, the downside of requiring larger sample sizes is limitations in data availability, often requiring reliance on public databases and thus compromise on the type of available data and possible studies.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies attempted the analysis of antimicrobial resistance on E . coli with machine learning and larger sample sizes [ 20 , 26 , 27 , 86 ]. However, the downside of requiring larger sample sizes is limitations in data availability, often requiring reliance on public databases and thus compromise on the type of available data and possible studies.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogen induced gut modulation can create an imbalance in the abundance of bacterial species i.e., some species outgrow known resident bacteria, leading to a dysbiosis of the gut microbiome and successful Salmonella colonization and antibiotic transfer (55,56). In this study, we observed that competition from commensal bacteria in reused litter significantly reduced S. Heidelberg population that acquired AR from E. coli strains harbored by neonatal chicks.…”
Section: Discussionmentioning
confidence: 65%
“…[ 36 ], but in this paper it was detected in S. Infantis isolate 8418/2948. However, the vgaC , streptogramin A resistance gene was detected frequently in S. Kentucky isolates and in a single S. Typhimuirum isolate from broiler chicken farms in British Columbia, Canada, by Maguire et al [ 37 ]. Resistance to tetracycline is a frequent phenotype in S. Infantis and it was not surprising that four out of seven S. Infantis isolates expressed resistance to this antibiotic by utilizing the efflux mechanism encoded either by tetA gene (1371/1 and 1981/1) or by tetA and tetK genes (8418/2948 and 9520/2).…”
Section: Resultsmentioning
confidence: 99%